La cláusula democrática - Covarrubias Velasco, Ana (Revista Mexicana de Política Exterior, 2022)
In this essay, the author ponders the so-called democratic clause, which despite its lack of novelty in international relations, strictly speaking, is becoming more important because of its connection with human rights protection. The article analyzes the changes that have occurred in Mexico’s foreign policy toward accepting and promoting this clause.